2017
DOI: 10.1371/journal.pone.0181973
|View full text |Cite
|
Sign up to set email alerts
|

Freezing during tapping tasks in patients with advanced Parkinson’s disease and freezing of gait

Abstract: IntroductionParkinson’s disease patients with freezing of gait also experience sudden motor blocks (freezing) during other repetitive motor tasks. We assessed the proportion of patients with advanced PD and freezing of gait who also displayed segmental “freezing” in tapping tasks.MethodsFifteen Parkinson’s disease patients with freezing of gait were assessed. Freezing of gait was evaluated using a standardized gait trajectory with the usual triggers. Patients performed repetitive tapping movements (as describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…To this effect, many research groups have used a variety of methods and approaches to understand the pathophysiological mechanisms behind FoG. Among the most notable approaches are behavioral and clinical measures ranging from gait and posture (7)(8)(9)(10)(11)(12)(13) to upper limb biomechanics (14), jaw displacement (15), saccade latency, velocity, and gain (16), audio-spinal reflex (17), handwriting measures (18), foot pedal measures (19), speech (20), electromyography (EMG) (21,22), and even rapid eye movement frequency (23). However, to explore the physiological changes specifically related to FoG in neurological pathways and their effect on motor control, it is necessary to detect efficacious neural biomarkers that may differentiate PD from healthy controls and PD subtypes from one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To this effect, many research groups have used a variety of methods and approaches to understand the pathophysiological mechanisms behind FoG. Among the most notable approaches are behavioral and clinical measures ranging from gait and posture (7)(8)(9)(10)(11)(12)(13) to upper limb biomechanics (14), jaw displacement (15), saccade latency, velocity, and gain (16), audio-spinal reflex (17), handwriting measures (18), foot pedal measures (19), speech (20), electromyography (EMG) (21,22), and even rapid eye movement frequency (23). However, to explore the physiological changes specifically related to FoG in neurological pathways and their effect on motor control, it is necessary to detect efficacious neural biomarkers that may differentiate PD from healthy controls and PD subtypes from one another.…”
Section: Introductionmentioning
confidence: 99%
“…Great efforts have been made to study neural features that differentiate PD patients who exhibit FoG (PDFoG+) vs. those who do not (PDFoG–). To accomplish this, the research tools that have been applied include functional near-infrared spectroscopy (fNIRS) ( 24 ), electroencephalography (EEG) ( 13 , 25 28 ), deep brain electrode-based recordings ( 26 , 29 33 ), and various neuroimaging tools such as volumetric magnetic resonance imaging (vMRI), diffusion MRI (dMRI), functional MRI (fMRI) ( 34 37 ), and positron emission tomography (PET) ( 35 , 36 ). It is well-known that each of these methods has advantages over the others, for example, the spatial vs. temporal resolution advantage held by fMRI over EEG, or the non-invasive vs. surgical advantage of EEG over deep brain electrode-based recordings.…”
Section: Introductionmentioning
confidence: 99%
“…A review study performed by Rovini et al [8] reported that there are a small number of studies that used sensor data from lower extremities. The most investigated motor tasks for analyzing motor impairments from lower extremities include freezing of gait [16], and timed up and go tests [17]. From a clinical point of view the leg agility test can be seen as the least useful test for measuring PD motor symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical practice, it is generally scored as part of the finger tapping and hand movement items [5,6], components of the Movement Disorders Society -Unified Parkinson's Disease Rating Scale (MDS-UPDRS) part III. However, in a study cohort consisting solely of patients with advanced PD and clinically confirmed freezing, FOUL was only detected in 5% of the trials and in only 3 out of 15 participants while being 'on' medication [6]. A possible explanation lies in the increased attentional level related to an examination in a lab environment, which may temporarily suppress patients' freezing [7].…”
Section: Introductionmentioning
confidence: 99%